The Black geographic : praxis, resistance, futurity - Hawthorne, Camilla A.; Lewis, Jovan Scott (Duke University Press, 2023)
"The contributors to The Black Geographic explore the theoretical innovations of Black Geographies scholarship and how it approaches Blackness as historically and spatially situated. In studies that span from Oakland to the Alabama Black Belt to Senegal to Brazil, the contributors draw on ethnography, archival records, digital humanities, literary criticism, and art to show how understanding the spatial dimensions of Black life contributes to a broader understanding of race and space. They examine key sites of inquiry: Black spatial imaginaries, resistance to racial violence, the geographies of racial capitalism, and struggles over urban space. Throughout, the contributors demonstrate that Blackness is itself a situating and place-making force, even as it is shaped by spatial processes and diasporic routes. Whether discussing eighteenth- and nineteenth-century abolitionist print records or migration and surveillance in Niger, this volume demonstrates that Black Geographies is a mode of analyzing Blackness that fundamentally challenges the very foundations of the field of geography and its historical entwinement with colonialism, enslavement, and imperialism. In short, it marks a new step in the evolution of the field. Contributors. Anna Livia Brand, C.N.E. Corbin, Lindsey Dillon, Chiyuma Elliott, Ampson Hagan, Camilla Hawthorne, Matthew Jordan-Miller Kenyatta, Jovan Scott Lewis, Judith Madera, Jordanna Matlon, Solange Muñoz, Diana Negrín, Danielle Purifoy, Sharita Towne"--